Collective mechanical adaptation of honeybee swarms. Issue 12 (December 2018) - Peleg, O.; Peters, J.; Salcedo, M.; Mahadevan, L.
Abstract HoneybeeApis mellifera swarms form large congested tree-hanging clusters made solely of bees attached to each other1 . How these structures are maintained under the influence of dynamic mechanical forcing is unknown. To address this, we created pendant clusters and subject them to dynamic loads of varying orientation, amplitude, frequency and duration. We find that horizontally shaken clusters adapt by spreading out to form wider, flatter cones that recover their original shape when unloaded. Measuring the response of a cluster to an impulsive pendular excitation shows that flattened cones deform less and relax faster than the elongated ones (that is, they are more stable). Particle-based simulations of a passive assemblage suggest a behavioural hypothesis: individual bees respond to local variations in strain by moving up the strain gradient, which is qualitatively consistent with our observations of individual bee movement during dynamic loading. The simulations also suggest that vertical shaking will not lead to significant differential strains and thus no shape adaptation, which we confirmed experimentally. Together, our findings highlight how a super-organismal structure responds to dynamic loading by actively changing its morphology to improve the collective stability of the cluster at the expense of increasing the average mechanical burden of an individual. Suspended clusters of honeybees withstand dynamic mechanical forcing from their environment. Experiments and simulations suggest that collective stability relies on individual bees responding to local variations in strain.